Perspektif Al-Qur’An tentang Kedudukan Penguasa dalam Penyelenggaraan Pendidikan - Asropah, Ade Elin (Tsamratul Fikri, 2023)
The government, acting as state administrators, has implemented different measures to address issues in national education, including the implementation of several national education plans. Nevertheless, despite the passage of time and the varying circumstances in different areas, the government's endeavours continue to be impeded. Indonesia's education system has shown improvement from the Old Order era to the New Order and continues to progress in the present day. Nevertheless, the current situation is deeply concerning and progressively intricate, making it challenging to choose where to initiate attempts for reform. Numerous education experts have put forth various strategies and solutions to address the issues in our national education system. However, the outcomes thus far have been disappointing. As a result, there is renewed emphasis on the roles and responsibilities of government authorities as state administrators to ensure the provision of high-quality education, as mandated by the constitution. The education system in Indonesia primarily emphasises procedural requirements and formalities to meet immediate pragmatic needs. It places greater importance on intellectual aspects and rationalism, while neglecting moral, ethical, and spiritual qualities. This nation must persist in acquiring knowledge, drawing lessons from history, acknowledging errors, gaining insights from other nations, and cultivating one's own abilities rather than merely imitating or adopting. It should remain firmly grounded in its national culture as necessary. Reflecting on the history of Islamic education, it is evident that Prophet Muhammad made significant efforts to transform the people of Mecca and Medina over a period of 23 years. Through the guidance of Allah SWT's revelations, he achieved remarkable success. The Al-Qur`an serves as a definitive manual for leading one's life. The Prophet's role as both a religious and state leader is closely tied to his guidance of the Koran, which emphasises moral, ethical, and spiritual principles. This advice is deeply based in the society's potential and cultural values, and aims to provide education.